(untitled) (Medico Legal Update, 2020)
Introduction: The childhood blindness due to retinopathy of prematurity (ROP) can be prevented if infants at risk are screened before the progression of the condition. The parental awareness on need of follow-ups for screening and identification of ROP will help in reducing the incidence of childhood blindness due to ROP. Method: In the present study an informative pamphlet was developed and distributed to find its effectiveness in improving the parents’ knowledge on retinopathy of prematurity. Quantitative research approach was used with pre-experimental pre-test post-test one group design. Conceptual framework used was General system theory by Ludwig Von Bertalanffy. Using convenience sampling method 30 parents of preterm babies were selected. The baseline proforma and knowledge questionnaire were administered and later an informative pamphlet about ROP were given. Post-test knowledge assessment was done 7 days after the exposure to pamphlet. Result and Discussion: The study finding showed an increase in the knowledge of parents on ROP after the exposure to pamphlet (Z=4.628, p=.001). An association was found between pre-test knowledge and previous parental knowledge on eye diseases in newborn babies (U=59, p=.048). The present study concludes that the pamphlet made by the researcher on ROP was effective in improving the parents’ knowledge about ROP.